Polymorphism in leaf metabolites in three different populations of Crataegus sinaica from South Sinai, Egypt - Hebatallah ALY; Shrouk MAHMOUD; Ahmed Ahmed EL-BAKRY (Notulae Scientia Biologicae)
Sinai hawthorn (Crataegus sinaica) is a wild tree native to Egypt, North Africa, and the Middle East. It is used for firewood and its leaves are utilized for grazing and medicinal purposes. The study aimed at identifying genotypes, optimal collection times, and localities for phytochemical variation in leaves. Fourteen genotypes were collected from three different locations in Saint Catherine Protectorate during the fruit ripening season and tested for primary and secondary metabolites content. Genotypic variation significantly influenced the content of the leaf phytochemicals.  Genotypes growing in Mosa Mountain had the highest content of metabolites compared to other locations. The superior genotype was G7 in August, G1 in September, and G9 in October, according to the pooled content of primary metabolites (PM). The best genotypes were G7 and G9 in August and September, and G6 in October, according to pooled secondary metabolite (SM) by collection time. The optimal time and location for the highest content of PM was September in Mosa Mountain for soluble sugars, Abohamman for soluble proteins. August at Algragania was the highest for carbohydrates. Among the studied SM, phenolics were most abundant across the study. September showed the highest content for flavonoids in Abohamman genotypes and in Mosa Mountain genotypes for phenolics and cardiac glycosides. The present study documented the significant differences in both primary and secondary metabolites for genotypes, location, and season. This is highly valuable for proper grazing, pharmaceutical research, restoration and sustainable development for the species, and for the desert’s harsh vulnerable ecosystem.